Evaluation of smoking habits among Turkish family physicians. (February 2014) - Baltaci, Davut; Bahcebasi, Talat; Aydin, Leyla Yilmaz; Ozturk, Serkan; Set, Turan; Eroz, Recep; Celer, Ahmet; Kara, Ismail Hamdi
Smoking is still a major public health problem in Turkey. It was aimed to investigate smoking prevalence and habits among Turkish family physicians. Cross-sectional study among physicians working in primary care settings was established. A self-administered study survey was applied. The surveys of 1233 family physicians were analyzed. The study included 704 (57.1%) male and 529 (42.9%) female physicians. Mean age (SD) was 38.94 (7.01) years. The proportions of the current, the former and never smokers among family physicians were 34.1%, 14.7% and 51.3%, respectively. Mean age (SD) of smoking initiation was 21.73 (5.04) years. Mean duration (SD) of smoking use was 14.61 (7.29) years. Proportion of current smoker in male physicians was quite higher than in female counterparts (36.9% vs. 30.4%; p  < 0.001). Mean age (SD) of smoking initiation in female was 21.42 (4.59) years, but in male was 22.33 (4.98) years ( p  = 0.36). In female physicians, mean age (SD) for quitting cigarette smoking was found higher than in male (35.85 (6.35) years vs. 33.09 (6.45) years; p  = 0.004). No significant difference between nicotine dependence (mean score (SD) of 3.76 (2.48) vs. 3.65 (2.82); p  > 0.05) and mean (SD) unit of cigarette a day (18.34(6.03) vs. 17.17 ± 6.79; p  > 0.05) between genders was observed. The number of male physicians who started smoking before faculty was higher than female counterparts (15.5% vs. 8.6%; p  = 0.023). In conclusion, the smoking prevalence among Turkish family physicians is considerably high.